A Gold(I) Complex Containing an Oleanolic Acid Derivative as a Potential Anti‐Ovarian‐Cancer Agent by Inhibiting TrxR and Activating ROS‐Mediated ERS. Issue 31 (25th March 2020) - Bian, Mianli; Sun, Ying; Liu, Yuanhao; Xu, Zhongren; Fan, Rong; Liu, Ziwen; Liu, Wukun
Abstract: Many cancer cells critically rely on antioxidant systems for cell survival and are vulnerable to further oxidative impairment triggered by agents generating reactive oxygen species (ROS). Therefore, the classical design and development of inhibitors that target antioxidant defense enzymes such as thioredoxin reductase (TrxR) can be a promising anticancer strategy. Herein, it is shown that a gold(I) complex containing an oleanolic acid derivative (4 b ) induces apoptosis of ovarian cancer A2780 cells by activating endoplasmic reticulum stress (ERS). It can inhibit TrxR enzyme activity to elevate ROS, mediate ERS and mitochondrial dysfunction, and finally leads to cell cycle arrest and apoptosis of A2780 cells. Notably, this complex inhibits A2780 xenograft tumor growth accompanied by increased ERS level and decreased TrxR activity in tumor tissues. Abstract : Au versus OC : A gold(I) complex containing an oleanolic acid derivative induces apoptosis of ovarian cancer (OC) cells by activating endoplasmic reticulum stress (ERS). It inhibits thioredoxin reductase (TrxR) enzyme activity to generate reactive oxygen species (ROS), mediates ERS and mitochondrial dysfunction, and finally leads to cell cycle arrest and apoptosis of A2780 cells. Notably, it inhibits xenograft OC tumor growth accompanied by increased ERS level and decreased TrxR activity in tumor tissues.